Bangladesh and The Role of Private Sector: Addressing Digital Divides - Roldan, Maria Divina Gracia Z. (Animo Repository, 2012)
Access to information and communication technologies (ICT) is seen as a key tool to provide economic growth both in developed and developing countries. Despite public and private ICT initiatives to increase ICT access and usage at a grassroots level, there is still a large digital divide (Norris 2003, Mazzarella 2010). Marginalized sectors in Asia, such as the rural folk, women, and low-income youth, remain unreached by the benefits which ICT is supposed to offer. In this paper, three approaches in Bangladesh to decrease the digital divide are analyzed: Grameenphone’s establishment of Community Information Centers (CICs), Grameenphone’s Village Phone program, and Cellbazaar. In what ways can the private sector, through its business initiatives, touch upon the issues of digital divide and social inclusion? By providing the needed infrastructure to spur usage and awareness of ICT in low-income communities, the private sector’s role as ICT provider and enabler is emphasized.